Clays and Clay Minerals, Vol. 54, No. 5, 587-597, 2006. - Kacmaz, H.; Kokturk, U. (The Clay Minerals Society, 2006)
The zeolites and coexisting minerals of the silicic vitric tuffs in the Alacatõ (C es° me) area, west of IÇ zmir (Turkey), were studied. Mordenite is the most abundant zeolite in tuffs of the AlacËatõ area and usually coexists with clinoptilolite-heulandite, smectite and calcite. Opal-CT was identified by means of its crystal morphology and EDX spectrum. Scanning electron microscopy (SEM) revealed the relative age relationships between the zeolites and coexisting minerals, namely mordenite, clinoptilolite-heulandite, smectite, calcite, and, in addition, opal-CT. Smectite consistently crystallized earlier than any of the zeolites, and it occasionally coats the outer walls of some of the vitric material. The zeolites are commonly located on the smectite, although some mordenites were observed to be in direct contact with glass shards that lacked a smectite coating. Clinoptilolite-heulandite formed after smectite and before mordenite. Opal- CT is seen to postdate both smectite and needle-shaped mordenite. Calcite was probably the latest mineral to crystallize in the AlacËatõ tuffs. The zeolites in the tuffs of the AlacËatõ area formed by dissolution of silicic vitric tuffs by Na- and Ca-rich thermal waters which passed through the fracture zone. The appearance of zeolites together with smectite along this zone may be attributed to a semi-open system which subdivided into smaller closed systems. Small changes in the pH and chemical composition of the thermal waters during alteration produced the corrosion effects observed by SEM. Small amounts of clinoptilolite- heulandite were corroded prior to crystallization of coexisting mordenite. The different compositions of the thermal waters were probably inherited from water that resulted from mixing of thermal and groundwaters.
Zeolites and Coexisting Authigenic Minerals in Miocene Tuffs of the Alace Ati (Cesme) Area, Turkey
Keywords: Periodicals; Geology; Alacati; Calcite; Clinoptilolite-heulandite; Geothermal; Miocene; Mordenite; Turkey; Zeolite